Identificação e mapeamento de marcadores associados a locos de resistência a virose do mosaico dourado em feijão caupi (Vignaunguiculata (L.) Walp.) - Rodrigues, Marciene Amorim (2011)
The objective of this work was the identification of markers linked to resistant genes to the cowpea golden mosaic virus (CGMV) through AFLP markers and the development and validation of SCAR markers linked to the resistance genes. For the study, the F2 population (286 individuals) resulting from the cross between IT97K-499-35, resistant genitor, and Canapu T16, susceptible, was used. The methodologies of Bulked Segregant Analysis and AFLP were used to identify markers linked to the resistance gene. The program JoinMap version 2.0 was used for construction of the map, adopting a minimum LOD of 3.0, a maximum recombination frequency of 0.45, and the Kosambi mapping function. Among the 196 combinations of AFLP primers tested, three markers linked to the resistance gene to CGMV were identified. The markers presented distances of 4.3 cM (E.AAC/M.CCC515), 14.2 cM (E.AGG/M.CTT280), and 16.8 cM (E.AAA/M.CAG352) of the resistance gene to golden mosaic, with the first two flanking it. The LOD scores were 50.4, 24.4, and 28.7, respectively. Eight SCAR markers were developed from the AFLP markers E.AAC/M.CCC515 and E.AAA/M.CAG352. In the eight combinations of SCAR primers tested among resistant and susceptible individuals of the F2 population, it was not possible to obtain the same segregation observed in the AFLP analysis. Efforts to develop SCAR markers efficient in detecting the resistance gene from AFLP markers obtained in the mapping of the gene that confers resistance to CGMV continue being done.